2023
DOI: 10.1371/journal.pone.0286131
|View full text |Cite
|
Sign up to set email alerts
|

Human presence and infrastructure impact wildlife nocturnality differently across an assemblage of mammalian species

Abstract: Wildlife species may shift towards more nocturnal behavior in areas of higher human influence, but it is unclear how consistent this shift might be. We investigated how humans impact large mammal diel activities in a heavily recreated protected area and an adjacent university-managed forest in southwest British Columbia, Canada. We used camera trap detections of humans and wildlife, along with data on land-use infrastructure (e.g., recreation trails and restricted-access roads), in Bayesian regression models t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Other species such as wolves (Canis lupus) or caribou (Rangifer tarandus tarandus) tend to avoid or change their behaviour in areas where humans recreate (Gill et al, under review;Rogala et al, 2011), which would result in a reduction in HWIs with rising park attendance. Future research should aim to identify the effects of increasing visitor volumes across species (e.g., Procko et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other species such as wolves (Canis lupus) or caribou (Rangifer tarandus tarandus) tend to avoid or change their behaviour in areas where humans recreate (Gill et al, under review;Rogala et al, 2011), which would result in a reduction in HWIs with rising park attendance. Future research should aim to identify the effects of increasing visitor volumes across species (e.g., Procko et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Guest volume is a pressing issue for park managers, as it strains operations and reduces the quality of the visitor experience (Manning, 2001;Prakash et al, 2019). The presence and behaviour of humans in protected areas can negatively impact wildlife through increased zoonotic disease transmission (Charron, 2002;Monahan et al, 2009), a loss of biodiversity (Nyhus, 2016), altered spatiotemporal patterns in habitat use, including habitat loss through avoidance, behavioural change (e.g., conditioning, tolerance, predator shield;Lopez Gutierrez et al, 2020;Procko et al, 2023), and changes in energetics (Corradini et al, 2021;Gaynor et al, 2018;Larson et al, 2016;Reed & Merenlender, 2008;Rogala et al, 2011;Sarmento & Berger, 2017;Whittington et al, 2022). Human sourced food and salts also act as attractants for many species, generating human-wildlife-interactions (HWIs) that can result in the destruction of individual animals (Hebblewhite et al, 2003;Vayro et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A 30-min independence threshold is common in most wildlife studies (Burton et al, 2015). We used the 1-min threshold for human detections because numerous independent recreationists are likely to use high-traffic trails within the larger 30-min window (Procko et al, 2022(Procko et al, , 2023. This method may have slightly underestimated visitors, as multiple individuals were recorded as a single detection event if they all pass the camera within 1 min of each other.…”
Section: Camera Trap Sampling and Image Processingmentioning
confidence: 99%
“…Human activity is widely recognized to influence wildlife diel activity patterns (Gaynor et al, 2018;Nickel et al, 2020). However, prior studies have indicated that the choice of how to characterize human activity-as a categorical or continuous variable-may impact results (Dertien et al, 2021;Procko et al, 2023). Therefore, we used two analyses to test whether elk adjust their diel activity patterns (i.e., hours of activity) to become more nocturnal in areas of higher recreation.…”
Section: Diel Activity Modelingmentioning
confidence: 99%
“…We sought to determine the best‐supported factors driving cougar occurrence in the boreal using camera traps (Burton et al., 2015). Camera traps are a useful tool for studying elusive, far‐ranging mammals that live in low densities and have been used effectively for cougars (Alexander & Gese, 2018; Guarda et al., 2017; Loonam et al., 2021; Procko et al., 2022, 2023). We collected data from a camera array deployed at the edge of the cougar's northeastern range in Alberta, Canada, relative to the proposed expansion front.…”
Section: Introductionmentioning
confidence: 99%